Digital Wars of the World-System: Technofeudalism and the Geopolitics of Streaming Platforms - Stelmach, Miłosz (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2026)
The article examines the contemporary streaming market from a geopolitical, economic, and technological perspective, portraying it as a battleground for cultural power and infrastructural dominance. Drawing on Immanuel Wallerstein’s world-systems theory, the author argues that digital audiovisual distribution not only reproduces but also intensifies the existing centre—periphery hierarchies through the technofeudal logic of platforms. The article explores four key tensions: internal competition among streaming services, the clash between traditional media industries and tech giants, the algorithmization of cultural access, and the geopolitical rivalry between the US and China. The author contends that the digital revolution in media distribution has not led to democratization, but instead has reinforced an oligopolistic system of control based on data, infrastructure, and algorithmic power.